DEVELOPMENT OF THE JUDICIAL SYSTEM OF UZBEKISTAN BASED ON THE EXPERIENCE OF THE FEDERAL CONSTITUTIONAL COURT OF GERMANY: RECOMMENDATIONS AND PROSPECTS (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
The report analyzes the model of the Federal Constitutional Court of Germany in order to adapt it to the conditions of Uzbekistan. Special attention is paid to the independence of the courts, constitutional control and protection of fundamental rights. Based on a comparative analysis, recommendations are proposed for improving the Constitutional Court of Uzbekistan, aimed at increasing confidence in the judicial system and strengthening the rule of law.